Potensi Pemanfaatan Ampas Kelapa Sebagai Biodiesel di Indonesia - I Wayan Koko Suryawan; Almira Davina Nastiti; Natasya Hikmat Putri; Adam Ali Marwan; Abid Naufal Khairan; Ariyanti Sarwono (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The potential for the use of coconut pulp as biodiesel fuel in Indonesia is very large because Indonesia is one of the largest coconut producing countries in the world. One of the conversion methods used to convert coconut pulp into biodiesel is the transesterification method using various catalysts. Based on several literature studies conducted, the yield produced using a CaO catalyst is 96.43% and using a KOH catalyst can reach up to 98.23% with the help of a microwave. The results of a survey that has been conducted on 30 grated coconut traders in various markets, the average coconut pulp produced every day is 20 kg/seller/day. The potential of biodiesel produced from the average amount of coconut dregs can reach up to 3.04 L using a KOH catalyst.